Rupture of pancreatic pseudocyst and therapeutic conduct: a case report - Graciano, Victor P.; Rodante, Andressa C.; Netto, Idari F. O.; Pin, Alessandro S.; Lacerda, Ludymilla O. P.; Pontes, Gabriela M.; Marciano, Ricardo D. (Brazilian Journal of Health and Biomedical Sciences, 2023)
Introduction: To report on a clinical case of a pancreatic pseudocyst that evolved to rupture and to understand the main therapeutic approaches adopted for pancreatic pseudocysts, thus fostering a better approach to such cases. Case report: Female patient, 30 years old, with pseudocystoadenoma and acute abdomen due to cystic rupture. Discussion: The therapeutic forms for pancreatic pseudocysts are expectant management, drainage (endoscopic and percutaneous) and surgical treatment. Results: The best approach addresses the treatment of the patient's clinical condition and pancreatic pseudocyst. For this to happen, a clinical evaluation,by means of complementary examinations, is required.